Coming out of the liberal closet. Think tanks and de-democratization in Poland. Issue 2 (17th February 2023) - Jezierska, Katarzyna
ABSTRACT: De-democratization is a global trend, with an increasing number of governments gradually dismantling democratic institutions and norms in their countries. De-democratization can be seen as an incremental crisis that radically redraws the sociopolitical order. This article is among the first to highlight external knowledge producers in autocratizing contexts. Relying on a unique data set of 40 interviews with Polish think tankers conducted before and after the Law and Justice party came to power in 2015 and began pushing the country in an authoritarian direction, the article analyses how liberal think tanks handle de-democratization. The findings show that autocratization entails a reconfiguration of the think tank space; i.e. think tanks aligning with the government blossom and think tanks opposing the government are marginalized through a lack of public funding and access to policymakers. Second, significant changes in think tank tactics, strategies, and identities, especially among liberal organizations, are exposed. The doxic mode through which liberal think tanks produce analyses and provide policy advice as "nonpartisan experts" has shifted to the use of contentious tactics and the assumption of an openly political identity as "democracy defenders".